An examination of techniques for raster-to-vector process and implementation of software package for automatic map data entry-mapscan - Khang, Bạch Hưng; Tạo, Ngô Quốc; Khôi, Phạm Ngọc; Mai, Lương Chi; Toàn, Đỗ Năng; Dũng, Nguyễn Đức; Thinh, Vu Van (Journal of Computer Science and Cybernetics, 2016)
The majority of commonly used manipulative techniques in computer-assisted cartography continue to require that the data be in  vector format. This situation has recently precipitated the  the requirement for  fast techniques for converting digital cartographic data from raster to vector format  for processing. This article concerns with examining the states in theses conversion techniques. In part one, algorithms to  perform all phases of  the raster-to-vector process are systematically outlined, and  then compared in the general term. Part two will describe the package for automatic map data entry MapScan, the algorithms implemented in which  are based on the fast techniques for converting  map raster data to vector format. With MapScan users are able to move printed maps or drawing into a mapping system much more quickly and easily compared to using traditional digitizer techniques.